Antibacterial Activity of New Synthesized Derivatives 3- Substituted Imidazo Benzothiazole from 2- amino- benzothiazole - Zainab Amer (Journal of Global Pharma Technology, 2016)
In this study, bromophenyl phencyl bromide was activated with 2-amino-benzothiazole to prepare 2-bromophenylimidazo (1, 2-a) benzothiazole [1]. Then prepare 2-bromophenyl imidazo (1,2-a) benzothiazol-3-carbaldyhade [2] of the interaction of 2-bromophenyl imidazo (1,2-a) benzothiazol [1] with the presence of POCl3, DMF and CH3Cl. After that I attended derivatives of Schiff bases [A1-A3] were synthesized from the reaction of 2-bromo phenyl imidazo (1, 2-a) benzothiazole-3-carpaldehyde [2] with different primary aromatic amines. New derivatives of oxazepine [B1-B3] were prepared from the interaction of amino compounds [A1-A3] with malic anhydride. The amino compounds [A1-A3] were then reacted with phenyliso cyanide to prepare new beta-lactam compounds [C1-C3]. At last, Schiff bases [A1-A3] were reduced to prepare new amino derivatives of imidazo (1, 2-a) benzothiazole [D1-D3]. All prepared compounds were characterized by melting point and FT-IR. Some of them characterized by 1H-NMR and13C-NMR spectra. Also, antibacterial activities to some prepared derivatives were studied by using different bacteria.Keywords: 2-amino-benzothiazole, Schiff bases, Oxazepine, Beta-Lactam, Reduction, Antibacterial activity.